ANALISIS KOMITMEN ORGANISASIONAL PEGAWAI DAMPAK FAKTOR KEPEMIMPINAN, BUDAYA ORGANISASI, DAN KARAKTERISTIK INDIVIDU (STUDI PADA PEGAWAI DINAS SOSIAL KABUPATEN BIREUEN) - Kamaruddin, Kamaruddin; Jamal, Jamal (LPPM-UNIKI, 2025)
The study was conducted on 54 employees of the Bireuen Regency Social Service. To determine the influence of Leadership, Organizational Culture and Individual Characteristics on Organizational Commitment. Implementing quantitative and associative research, with path analysis using SMART-PLS. Based on the results of the study, it can be concluded that Leadership has a positive and significant effect on organizational commitment. Organizational culture has a positive and significant effect on organizational commitment. And Individual Characteristics Have a Positive and Significant Effect on Organizational Commitment. Leadership Has a Positive Relationship with Individual Characteristics, Leadership is Positively Related to Organizational Culture and Organizational Culture is Positively Related to Individual Characteristics. The influence of leadership, organizational culture, and individual characteristics simultaneously on organizational commitment is 77.3%.